[Teaching a lesson ; Life in a monastery ; Dinosaurs alive [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1991)
Militant teachers go on a hunger strike to protest their removal from their jobs by Secretary Isidro Carino for leading a strike in 1990. In a Benedictine Abbey in Bukidnon, the monks lure a rigorous work and prayer life. Animated dinosaurs facscinates winners and open their minds to life million years ago.
Teaching a lesson (14 min.) -- Life in a monastery (16 min.) -- Dinosaurs alive (11 min.)
VHS.
Keywords: Monastery of Transfiguration (Bukidnon).; Strikes and lockouts (Teachers) -- Philippines -- Manila; Amusement parks -- Philippines -- Manila; Benedictine monks (Bukidnon); Monastic and religious life -- Philippines -- Bukidnon